Structured Content Analysis of Cases: A Complementary Method for Organizational Research - Jauch, Lawrence R.; Osborn, Richard N.; Martin, Thomas N. (Academy of Management Review, 1980)
In this article, we introduce a comparatively new method that uses case materials for the development and testing of hypotheses. After comparing cases to questionnaires as a data source, we explain the key role of the content analysis schedule, and provide an illustration centering on environmental volatility.